Male hypogonadism - brief review of symptoms, types and ways of treatment - Ewa Tywanek; Paulina Trojanowska; Jakub Wronecki; Katarzyna Wiśniewska-Ślepaczuk; Robert Jan Łuczyk (Kazimierz Wielki University, 2021)
Appropriate concentration of androgens is necessary for general men's health, especially for development and maintain reproductive and sexual function, as well as metabolic balance. The state  of deficiency of testosterone or its inadequate action, as well as inability to produce good quality semen is called hypogonadism. Depending on the function of the testicles, production of androgens and sperm is also conditioned on hypothalamus-pituitary axis, metabolic status and age of the individual. Considering that, hypogonadism of primary, secondary, functional or late-onset origin may be recognised. As it concerns susceptible matter of sexual and reproductive health, it requires special interest of differently clinicians, i.e. endocrinologists, andrologists or urologists.